Cardiovascular outcomes after curative prostate cancer treatment: A population-based cohort study - Kjellstadli, Camilla; Forster, Rachel B.; Myklebust, Tor Å.; Bjørge, Tone; Bønaa, Kaare H.; Helle, Svein I.; Kvåle, Rune (Frontiers in Oncology, 2023)
Objective: To investigate differences in cardiovascular disease (CVD) morbidity and mortality after radical prostatectomy or definitive radiotherapy with or without androgen deprivation therapy (ADT). Materials and methods: We used population-based data from the Cancer Registry of Norway, the Norwegian Patient Registry and the Norwegian Cause of Death Registry including 19 289 men ≤80 years diagnosed with non-metastatic prostate cancer during 2010-2019. Patients were treated with radical prostatectomy or definitive radiotherapy. We used competing risk models to compare morbidity from overall CVD, acute myocardial infarction (AMI), cerebral infarction, thromboembolism, and CVD-specific mortality for the overall cohort and stratified by prognostic risk groups. Results: After a median follow-up time of 5.4 years (IQR 4.6 years), there were no differences in adjusted rates of AMI, cerebral infarction, and CVD-specific death between radical prostatectomy and definitive radiotherapy in any of the prognostic risk groups. Rates of overall CVD (0.82; 95% CI 0.76-0.89) and thromboembolism (0.30; 95% CI 0.20-0.44) were lower for definitive radiotherapy than radical prostatectomy during the first year of follow-up. After this overall CVD rates (1.19; 95% CI 1.11-1.28) were consistently higher across all risk groups in patients treated with definitive radiotherapy, but there were no differences regarding thromboembolism. Conclusions: During the first years after treatment, no differences were found in rates of AMI, cerebral infarction, and CVD-specific death between radiotherapy and radical prostatectomy in any of the prognostic risk groups. This suggests that ADT use in combination with radiotherapy may not increase the risks of these outcomes in a curative setting. The increased overall CVD rate for definitive radiotherapy after the first year indicates a possible relationship between definitive radiotherapy and other CVDs than AMI and cerebral infarction.